2006
DOI: 10.1177/107110070602700605
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Achilles Tendon Lengthening on Ankle Dorsiflexion: A Cadaver Study

Abstract: The Achilles tendon is the anatomical structure that limits ankle dorsiflexion, even when the tendon is lengthened. There was a linear relationship between the length of the Achilles tendon and the range of ankle dorsiflexion in this cadaver model. Ankle dorsiflexion would appear to be a clinically useful indicator of tendon length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…Importantly, and as hypothesized, significantly increased Achilles tendon elongation was only seen if the ankle was immobilized at maximal dorsiflexion (20°) for 1 or 3 weeks. Clinical data suggest that Achilles tendon lengthening can be correlated with poor clinical outcomes and enduring changes in ankle dorsiflexion . In our model, even short immobilization (1 week) at 20° led to a significantly longer tendon than did immobilization in full plantarflexion (160°), and this corresponded with diminished propulsion force off the injured limb during ambulation post‐injury.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Importantly, and as hypothesized, significantly increased Achilles tendon elongation was only seen if the ankle was immobilized at maximal dorsiflexion (20°) for 1 or 3 weeks. Clinical data suggest that Achilles tendon lengthening can be correlated with poor clinical outcomes and enduring changes in ankle dorsiflexion . In our model, even short immobilization (1 week) at 20° led to a significantly longer tendon than did immobilization in full plantarflexion (160°), and this corresponded with diminished propulsion force off the injured limb during ambulation post‐injury.…”
Section: Discussionmentioning
confidence: 64%
“…Clinical data suggest that Achilles tendon lengthening can be correlated with poor clinical outcomes and enduring changes in ankle dorsiflexion. 11,32 In our model, even short immobilization (1 week) at 20˚led to a significantly longer tendon than did immobilization in full plantarflexion (160˚), and this corresponded with diminished propulsion force off the injured limb during ambulation post-injury. This finding suggests that dorsiflexed immobilization, or delayed treatment, may be associated with reduced push-off strength in endrange plantarflexion, mirroring an outcome seen clinically in humans.…”
Section: Discussionmentioning
confidence: 66%
“…Passive forces may also occur in other joint structures (e.g. bone, ligaments, skin), although the Achilles tendon has been found to be the primary structure limiting ankle joint dorsiflexion, and thus is probably the major contributor to passive force within a physiological joint range of motion (Costa et al, 2006). A sensitivity analysis found that any errors in predicting reductions in passive muscle force during MVC will have a small effect on the shape of the F-L curve and the assessment of subjectspecific L 0 ; when the reduction in passive forces is ignored, the estimate of L 0 is altered by less than 1% (Fig.A2B).…”
Section: Influence Of Passive Sol Force On Estimates Of Lmentioning
confidence: 99%
“…The range of ankle dorsiflexion was most influenced by the length of the Achilles tendon 28) . The division of the other tendons and the capsular tissue around the ankle joint did not affect the range of ankle dorsiflexion.…”
Section: Discussionmentioning
confidence: 98%